Altered Temporal Organization of Brief Spontaneous Brain Activities in Patients with Alzheimer's Disease. (15th January 2020) - Ma, Xiangyu; Zhuo, Zhizheng; Wei, Lijiang; Ma, Zhe; Li, Zhaoxia; Li, Haiyun; ,
Highlights: The average dwell time of activity in DMN is shortened in AD. The system entropy of the brain state-space increases in AD. The alteration of temporal organization may associate with CSF biomarkers. Abstract: The alterations of dynamic brain functions in Alzheimer's disease (AD) remain far from well understood. In this study, using functional magnetic resonance imaging (fMRI) data, we adopted a co-activation pattern (CAP) approach, which relies on very few assumptions, to explore the differences of brain dynamics among healthy elderly, patients with early amnestic mild cognitive impairment (MCI) and patients with AD. Briefly, k-means clustering was applied to all fMRI frames from the three groups and generated a set of reproducible CAPs. We found the obtained CAPs showed high correspondence to the well acknowledged functional networks including default mode network (DMN), executive control network and visual networks, etc. Different from previous CAP-based studies, we further quantitatively analyzed the temporal dependence of the CAPs using multiple parameters. Primary findings include, for AD and MCI compared with NC, the decreased mean fraction of occurrence and persistence of DMN related CAPs, which indicates the typical DMN damage; the increased/decreased mean persistence of ventral/dorsal visual network related CAPs, which may associate with the visuospatial disorder of patients with AD pathology; the elevated transition and CAP entropies and multiple alterations of CAP transition probabilities, which imply the altered mode of information flow and lifted system uncertainty in AD brains. We also found correlations of proposed measurements to cerebrospinal fluid biomarkers and neuropsychological scores. This study verified the AD-related alteration found by traditional FC analysis, and proposed several new biomarkers which have the potential for assisting AD treatment and early diagnosis.